To lead or not to lead? Prospective controlled study of emergency nurses' provision of advanced life support team leadership. Issue 9 (19th August 2005) - Gilligan, P; Bhatarcharjee, C; Knight, G; Smith, M; Hegarty, D; Shenton, A; Todd, F; Bradley, P
Abstract : Background and objectives: In many emergency departments advanced life support (ALS) trained nurses do not assume a lead role in advanced resuscitation. This study investigated whether emergency nurses with previous ALS training provided good team leadership in a simulated cardiac arrest situation. Methods: A prospective study was conducted at five emergency departments and one nurses' association meeting. All participants went through the same scenario. Details recorded included baseline blood pressure and pulse rate, time in post, time of ALS training, and subjective stress score (1 = hardly stressed; 10 = extremely stressed). Scoring took into account scenario understanding, rhythm recognition, time to defibrillation, appropriateness of interventions, and theoretical knowledge. Results: Of 57 participants, 20 were ALS trained nurses, 19 were ALS trained emergency senior house officers (SHOs), and 18 were emergency SHOs without formal ALS training. The overall mean score for doctors without ALS training was 69.5%, compared with 72.3% for ALS trained doctors and 73.7% for ALS trained nurses. Nurses found the experience less stressful (subjective stress score 5.78/10) compared with doctors without ALS training (6.5/10). The mean time taken to defibrillate from the appearance of a shockable rhythm on the monitor by the nurses and those SHOs without ALS training was 42 and 40.8 seconds, respectively. Conclusion: ALS trained nurses performed as well as ALS trained and non ALS trained emergency SHOs in a simulated cardiac arrest situation and had greater awareness of the potentially reversible causes of cardiac arrest. Thus if a senior or middle grade doctor is not available to lead the resuscitation team, it may be appropriate for experienced nursing staff with ALS training to act as ALS team leaders rather than SHOs.